Writing and cognition research and applications - Torrance, Mark.; Waes, L. van (Luuk); Galbraith, David, 1954- (Amsterdam ; Boston : Elsevier, 2007)
Writing is central to the functioning of developed societies. However, the psychological processes that allow us to transform complex ideas into language and express them on paper or computer screen are poorly understood. "Writing and Cognition" goes some way towards remedying this. It describes new and diverse work both by field leaders and by newer researchers exploring the complex relationships between language, the mind, and the environments in which writers work. Chapters range in focus from a detailed analysis of single-word production to the writing of whole texts. They explore the basic processes involved in writing, the effects of writing on thought and how these vary across different educational and workplace contexts: How do student writers differ in how they approach their text? What processes are associated with the transformation of knowledge during writing? How do the writers of press releases balance the demands of message and reader? Where do writers look when they write? Is memory retrieval easier in writing or when speaking? How does dyslexia affect text production? How does writing by speech-input differ from traditional keyboarding? This volume is essential reading for writing researchers. It will also interest educators, linguists, psychologists, psycholinguists, and anyone who wants to find out more about how thought is transferred to the page. It investigates the psychological processes that allow us to transform complex ideas into language and express them. The chapters examine a wide range of writing contexts and issues. Contributors include field leaders and newer researchers, allowing for a diversity of opinion.
Parallel processing before and after pauses : a combined analysis of graphomotor and eye movements during procedural text production / Denis Almargot, Christophe Dansac, David Chesnet, Michel Fayol -- From written word to written sentence production / Guido Nottbusch, Rudiger Weingarten, Said Sahel -- Influence of typing skill on pause-execution cycles in written composition / Rui Alexandre Alves, Sao Luis Castro, Liliana de Sousa, Sven Stromqvist -- The word-level focus in text production by adults with reading and writing difficulties / Asa Wengelin -- GIS for writing : applying geographical information systems techniques to data mine writings' cognitive processes / Eva Lindgren, Kirk P.H. Sullivan, Urban Lindgren, Kristyan Spelman Miller -- Verbal and visual working memory in written sentence production / Ronald T. Kellogg, Thierry Olive, Annie Piolat -- Effects of note-taking and working-memory span on cognitive effort and recall performance / Annie Piolat -- The dynamics of idea generation during writing : an online study / Huub van den Bergh, Gert Rijlaarsdam -- Skilled writers' generating strategies in L1 and L2 : an exploratory study / Sophie Beare, Johanne S. Bourdages -- The writing superiority effect in the verbal recall of knowledge : sources and determinants / Joachim Grabowski -- The effect of writing on phonological awareness in Spanish / Sofia A. Vernon -- Developmental trends in a writing to learn task / Perry D. Klein, Jennifer S. Bowman, Melanie P. Prince -- Approaches to writing / Ellen Lavelle -- Cognitive processes in discourse synthesis : the case of intertextual processing strategies / Rachel Segev-Miller -- Preformulation in press releases : what the writing process tells us about product characteristics / Kim Sleurs -- Talking to write : investigating the practical impact and theoretical implications of speech recognition (SR) software on real writing tasks / Noel Williams, Peter Harley, Vanessa Pittard -- How do writers adapt to speech recognition software? The influence of learning styles on writing processes in speech technology environments / Marielle Leijten -- Longitudinal studies of the effects of new technologies on writing : two case studies / James Hartley -- Learning by hypertext writing : effects of considering a single audience versus multiple audiences on knowledge acquisition / Elmar Stahl, Rainer Bromme, Marc Stadtler, Rafael Jaron -- Supporting individual views and mutual awareness in a collaborative writing task : the case of Col-laboracio / Henrry Rodriquez, Kerstin Severinson Eklundh.
Includes bibliographical references (p. [335]-363) and indexes.
Description based on print version record.
Keywords: Writing -- Psychological aspects; Authorship -- Psychological aspects; Cognitive styles; Psycholinguistics; Writing skills; Language Arts & Disciplines -- Linguistics -- General; Language Arts & Disciplines -- Composition & Creative Writing